Plant Regulators on Vegetative Growth of 'Tommy Atkins' Mangoes - Mouco, M. A. do C.; Ono, E. O. [UNESP]; Rodrigues, J. D. [UNESP]; Silva, G. J. N.; Lu, P. (Int Soc Horticultural Science, 2013)
Paclobutrazol applied to the soil is used for the production management of mango in most of orchards on the semiarid region. However, it is necessary to identify other plant growth regulators that might be applied to the leaves, so as to minimize the risk of residues in the soil and plant. The present paper has the purpose to evaluate the effect of plant regulators in the management of vegetative growth on mangoes 'Tommy Atkins'. Three plant growth regulators, sprayed to the leaves, were evaluated: prohexadione-Ca, ethyl-trinexapac and chlormequat chloride, applied in two dosages, and compared to paclobutrazol applied to the soil. In order to compare the effects of the treatment, data were recorded on the vegetative growth ( number and length of the shoots). Furthermore, the levels of gibberellins in the apical area of the shoots of 'Tommy Atkins' were quantified, from the beginning of the experiment until the beginning of floral induction. The results showed that sprayings with prohexadione- Ca, trinexapac-ethyl and chlormequat chloride in a dosage of 1.5 g a.i. plant(-1) plant was as efficient as a dose of 4.0 g a.i. plant(-1) of paclobutrazol applied to the soil, regarding the regulation of vegetative growth of 'Tommy Atkins'.
Keywords: Mangifera indica; paclobutrazol; prohexadione-Ca; ethyl-trinexapac; chlormequat chloride; gibberellin